Inhibition of the mosquito transmission of Plasmodium berghei by Malarone (atovaquone-proguanil). - Butcher, G; Mendoza, J; Sinden, R (2000)
Sera from patients treated with atovaquone-proguanil (Malarone) have previously been shown to inhibit the mosquito transmission of Plasmodium falciparum, though the inhibition was not complete and the effect declined 2 weeks after treatment. In marked contrast, the inhibition of transmission of P. berghei by human sera (fed to mosquitoes, with P. berghei gametocytes, via membrane feeders) from volunteers treated with atovaquone-proguanil was total up to day 28 post-treatment and still very significant at day 56. In view of the short half-lives of atovaquone and proguanil, this was unexpected, and further experiments, reported here, were undertaken. In contrast to the incomplete blockade of infectivity of P. falciparum by serum taken 4 days post-treatment, such serum was totally inhibitory against P. berghei at a 1:10,000 dilution, indicating a remarkable sensitivity of P. berghei and demonstrating an unusual difference between the two Plasmodium species in response to a drug. The inhibitory effect on P. berghei after day 4 was caused by atovaquone and mainly through blockade of development from ookinete to oocyst. Despite previous information on the rapid elimination of atovaquone by patients, the present data indicate that low concentrations of this drug may persist in the plasma for some weeks after treatment.